Does aspirin have a role in preventing unprovoked recurrent thromboembolism? - Yenny Yenny (Faculty of Medicine, Universitas Trisakti, 2013)
Venous thromboembolism (VTE), comprising deep vein thrombosis (DVT) and pulmonary embolism (PE), is a frequently recurring and serious complication after cessation of anticoagulant therapy. Several studies indicate that 10 years after cessation of anticoagulant therapy the risk of recurrent VTE is 39.9% and nearly 50% for unprovoked VTE.